2018
DOI: 10.2147/ppa.s179031
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine and adherence to antiepileptic drug therapy among epilepsy patients: a systematic review

Abstract: PurposeTo identify the use pattern of complementary and alternative medicine (CAM) and its impact on antiepileptic drug (AED) adherence among patients with epilepsy.MethodPotential studies were identified through a systematic search of Scopus, Science Direct, Google Scholar, and PubMed. The keywords used to identify relevant articles were “adherence,” “AED,” “epilepsy,” “non-adherence,” and “complementary and alternative medicine.” An article was included in the review if the study met the following criteria: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 61 publications
2
41
3
Order By: Relevance
“…Similar to the patient and disease-related dimensions, we did not find statistically significant associations with adherence for any of the therapy-related factors. This differs from other studies which highlighted significant associations between complicated treatment regimen and ASM adverse effects with poor medication adherence [6,19,25,33]. A possible reason for the discrepancies in our findings may be attributed to our inadequate sample size.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Similar to the patient and disease-related dimensions, we did not find statistically significant associations with adherence for any of the therapy-related factors. This differs from other studies which highlighted significant associations between complicated treatment regimen and ASM adverse effects with poor medication adherence [6,19,25,33]. A possible reason for the discrepancies in our findings may be attributed to our inadequate sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…Patient-related factors such as treatment control, concern, understanding and identity were not found to be statistically different. However, previous studies have shown that patient understanding and perceived lack of benefit of ASM therapy were significant predictors of non-adherence [6,19,37]. This contradiction is possibly attributed to the education level of our patients and the high scores in patients' illness perception which is similar in both the adherent and non-adherent groups in our study.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In 1998, Astin found that dissatisfaction with and distrust in biomedicine was a significant predictor in alternative, but not in complementary use (Astin, 1998). In the latter group, patient characteristics such as "holistic thinking" and "spirituality" (Astin, 1998) were significant predictors, alongside psychosocial etiology as a naive theory of illness causation (Farrukh, Makmor-Bakry, Hatah, & Tan, 2018). According to Hunt, employing CAM as an alternative to (as opposed to complementing) biomedicine reached 30% among all British CAM users in 2010 (Hunt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%